Upregulation of TREM2 expression in M2 macrophages promotes Brucella abortus chronic infection - Wang, Jingyu; Yan, Zhirong; Zhang, Weiyu; Liu, Xiaofeng; Wang, Jun; Peng, Qisheng (Frontiers in Immunology, 2024)
Brucella abortus (B.abortus) is a zoonotic bacterial pathogen that causes chronic host infections. The eradication of brucellosis using antibiotic therapy is often incomplete or slow. In a mouse model, the predominance of alternatively activated macrophages (also known as M2) plays an essential role in sustaining chronic infection. The underlying functional mechanism by which M2 sustains chronic infection remains unclear. Here, we show that B. abortus can enter M2 via triggering receptor expressed on myeloid cells 2 (TREM2) and promotes the upregulation of TREM2 expression of M2 in a type IV secretion system (T4SS)-dependent manner. Increased TREM2 enhances B. abortus growth within M2 by suppressing intracellular ROS production, preventing M2 pyroptosis via suppression of mitochondrial ROS (mROS), and promoting M2 proliferation by increasing β-catenin expression. In line with these results, downregulation of TREM2 expression suppressed B. abortus intracellular growth and M2 proliferation and induced M2 pyroptosis. In our mouse model, upregulation of TREM2 expression sustained the accumulation of M2 and B. abortus chronic infection, whereas downregulation of TREM2 expression restricted M2 proliferation and chronic infection. Collectively, our results suggest that targeting TREM2 may be a potential adjunct to antibiotic therapy for the prevention of chronic Brucella infection.